2013
DOI: 10.1097/scs.0b013e31829ac8e2
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computer-Guided Flapless Dental Implant Surgery (NobelGuide) and Immediate Function to Support a Fixed Full-ArchProsthesis inFresh-Frozen Homologous Patients with Bone Grafts

Abstract: The behavior of fresh-frozen homologous bone (FFB) when used in combination with computer-guided implant surgery has not been investigated yet, and there is a lack of clinical evidence in the literature. The purpose of this retrospective study is to evaluate the implant survival and related fixed full-arch prostheses at the 1- to 5-year follow-up when performed with immediate function using a flapless surgical procedure and computer-aided technology (NobelGuide; Nobel Biocare AB, Goteborg, Sweden) in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In Germany for example, around 700,000 patients are under conventional oral anticoagulant therapy such as Vitamin‐K inhibitors and the number of affected people will certainly increase due to the demographic development (Nocini et al. ). Since minor dental surgical treatments like tooth extractions are one of the most common procedures in health care, there will always be the question of managing this patient cohort among dentists, general practitioners and cardiologists, as well as affected patients (Doonquah & Mitchell ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany for example, around 700,000 patients are under conventional oral anticoagulant therapy such as Vitamin‐K inhibitors and the number of affected people will certainly increase due to the demographic development (Nocini et al. ). Since minor dental surgical treatments like tooth extractions are one of the most common procedures in health care, there will always be the question of managing this patient cohort among dentists, general practitioners and cardiologists, as well as affected patients (Doonquah & Mitchell ).…”
mentioning
confidence: 99%
“…Anticoagulant drugs are prescribed for a large number of diseases and commonly used in patients with atrial fibrillation, artificial heart valves, deep vein thrombosis, myocardial infarction, and pulmonary embolisms (Al-Mubarak et al 2006;Wahl et al 2015). In Germany for example, around 700,000 patients are under conventional oral anticoagulant therapy such as Vitamin-K inhibitors and the number of affected people will certainly increase due to the demographic development (Nocini et al 2013). Since minor dental surgical treatments like tooth extractions are one of the most common procedures in health care, there will always be the question of managing this patient cohort among dentists, general practitioners and cardiologists, as well as affected patients (Doonquah & Mitchell 2012).…”
mentioning
confidence: 99%
“…Each patient received an orthopantomography (OPG) and a computed tomography (CT) for evaluation of bone volume and planning of implantsupported restoration. All virtual implant planning was performed by the same expert operator, following the manufacture guidelines for guided implant surgery (NobelGuide5, Nobel Biocare Holding AG, Zurich, Switzerland) [19][20][21][22]. Radiographic templates were prepared for completely edentulous patients.…”
Section: Presurgical Protocolmentioning
confidence: 99%
“…It was reported that flapless implant insertion caused less peri-implant loss than implant insertion with flap preparation. Therefore, the flapless procedure represents a protective and promising method in implant surgery [1,6,7] Laleman et al [8] reported a systemic review for guided implant surgery in the edentulous maxilla, nevertheless, almost all implants included in this review were placed without flaps.…”
Section: Introductionmentioning
confidence: 99%